IMPLEMENTASI PERATURAN DAERAH KOTA PALANGKA RAYA NOMOR 22 TAHUN 2014 TENTANG RETRIBUSI PELAYANAN PERSAMPAHAN/KEBERSIHAN (STUDI TERHADAP PEDAGANG KREATIF LAPANGAN DALAM PELAKSANAAN CAR FREE DAY DI BUNDARAN BESAR KOTA PALANGKA RAYA) - Eriani; Ira Zuraida; Suprayitno (Journal Ilmu Sosial, Politik, dan Ilmu Pemerintahan, 2019)
Cleanliness Retribution is one of the sources that has the potential to increaseRegional Original Income, especially in the implementation of Car Free Day in the?Bundaran Besar? Palangka Raya City. This can be seen from its contribution to theRegional Original Income which is quite large and always increases every year. Thiscleanliness levy serves to fulfill the routine needs of the regional treasury, regulate thehealth of the community and the environment, as well as to cover the costs ofadministering waste / cleaning services. This study aims to find out, analyze and describehow the implementation of Regional Regulations Regarding Cleaning Levies AgainstCreative Traders of Car Free Day in the ?Bundaran Besar? Palangka Raya City. Inaddition, it is also to analyze the factors that influence the implementation of RegionalRegulations concerning Cleaning Levies Against Creative Traders in the Car Free Day?Bundaran Besar? Palangka Raya City. The author uses the theory of policyimplementation from George C. Edward III which consists of four indicators, namelycommunication, resources, disposition and bureaucratic structure. This study uses aQualitative Approach with data collection techniques that include Observation, Interviewand Documentation. From the results of the study, it was found that the Implementation ofRegional Regulations concerning Hygiene Levies on Creative Traders of Car Free Day?Bundaran Besar? Palangka Raya City is still not optimal, so it still needs to beaddressed.The conclusions from the research on the implementation of the RegionalRegulations on Hygiene Levies Against Creative Traders of Car Free Day ?BundaranBesar? Palangka Raya City are still not optimal, this is caused by the first, the lack ofsupervision by the management agency so that it is prone to irregularities. Secondly, therewas no socialization regarding the content and purpose of the Regional Regulationsconcerning Cleanliness retribution. Third, the management office is less aware of thepotential for cleaning fees at the location.